FAKTOR YANG MEMPENGARUHI KONSUMSI IKAN PADA BALITA DI WILAYAH PESISIR DAN PERBUKITAN KOTA SEMARANG - Azkia, Bardiatul; Suyatno, Suyatno; Kartini, Apoina (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Fish consumption in Indonesia in 2017 is 46.49 kilograms/capita/year, has not reach the target of national in 2017 which is 47.12 kilograms/capita/year or 54.49 kilograms/capita/year in 2019. Fish has many nutritional benefits especially for toddlers. There are several things that cause toddlers don’t consume fish, one of which is region’s topography. This research was conducted to determine the factors that influence fish consumption in infant base on regional topography. The type of research is observational with cross sectional research design. Population is toddlers with samples are 98 children, selected by simple random sampling method. The study was conducted using a questionnaire and FFQ sheets. Data analysis using Pearson statistical test, independent t-test, and multiple linear regression test. The results showed that toddlers in the coastal consumed more types of marine fish, while toddlers in the montainous consumed more types of land fish and processed fish. The fish consumption of both location areas fall into the category of low consumption frequency. The average amount of fish consumption in toddlers of coastal is 70,68 kg/capita/year, more than the average of mountainous which is 40,80 kg/capita/year p<0.05. Fish consumption in toddler in coastal is positively related to mother’s nutritional care pattern and economic access (p<0.05), while in mountainous is positively related to mother’s knowledge, child’s preference on fish, mother’s nutritional care pattern, and the availability of fish (p<0.05). It can be concluded that mother’s nutritional care pattern is variable that affects fish consumption in both location.